Effects of the use of contraceptives: a case of women in the Greater Accra and Ashanti regions of Ghana - Antwi, Sara Agyemang; Appiah, Jemima Aggrey; Adu, Abenaa Owusuaa (International Journal Of Community Medicine And Public Health, 2024)
Background: Contraceptive use during a woman's reproductive years can help prevent unintended pregnancies, maternal deaths, and other non-reproductive problems. However, there is also a risk of running into various health challenges. The study aimed at finding out if women in the Greater Accra and Ashanti regions of Ghana encounter health issues during and after use of contraceptives was conducted. Methods: Questionnaires were administered to 600 women out of which 401 responses were carefully gleaned for analysis using SPSS version 25. The questionnaire probed side and adverse effects women encountered in their use of contraceptives as well as the types of contraceptives they preferred. Results: The study revealed that the use of contraceptives was widely prevalent, especially amongst women aged 21-30 years (61.8%). The preferred types of contraceptives were the oral-progestin only (42.9%) and combined oral contraceptives (31.4%). Spotting or bleeding between periods (menstrual-related) was the highest reported side effect (33.2%), followed by weight gain (metabolic-related), 21.7%. Pearson’s Chi squared test showed an association between the age of respondents and the choice of contraceptive type at p<0.01. Hypertension and deep vein thrombosis (DVT) were the highest reported adverse effect (10.2% and 9.2% respectively). Conclusions: It was concluded that contraceptive use (especially the oral type) may cause discomfort with the side effects reported in women of reproductive age and it may be a contributing factor to other health conditions in susceptible women.